Laboratory and Benchtop Performance of a Mealtime Insulin-Delivery System. (July 2018) - Dreon, Darlene M.; Hannon, Trevor M.; Cross, Brett; Carter, Brett J.; Mercer, Nicholas S.; Nguyen, Jason H.; Tran, Andy; Melendez, Peter A.; Morales, Nancy; Nelson, Jonathan E.; Tan, Meng H.
Background: A basal bolus insulin regimen requires multiple daily insulin injections, which might discourage patient adherence. As a potential solution, a mealtime insulin-delivery system—a 3-day wearable bolus-only patch—was designed to manually administer mealtime insulin discreetly by actuating buttons through clothing, without the need for multiple needle sticks. Method: Extensive functional testing of the patch included dose accuracy (from initial fill of the device to empty), pressure-vacuum leak testing, last-dose lockout and occlusion detection (safety alert features that lock the dosing buttons when no insulin is delivered), assessments of insulin drug stability, toxicological risk (including chemical testing), and system biocompatibility. Results: Dosing accuracy was 2 units ±10% (with U-100 insulin) over a range of environmental conditions, with ≥95% reliability and confidence. The fluid seal performance and the safety alert features performed with ≥95% reliability and ≥95% confidence. The system met acceptable standards for insulin (U-100 lispro and aspart) stability for its intended 3-day use, in addition to the operational requirements. The toxicological risk assessment and demonstrated biocompatibility suggested that the patch is safe for human use. Conclusions: Benchtop performance showed that the bolus-only patch is a safe, accurate, and reliable device for mealtime insulin delivery.